Where on Earth is Gállogieddi? Márkomeannu and the practices of decolonisation in the Markasami area - Erika De Vivo (Anticus Press, 2019)
This paper aims at providing an outline of Márkomeannu,a Sami cultural festival held each July at Gállogieddi (Norland, Norway). Sami festivals are important cultural events, as theyepitomize the current Sami cultural revival. After decades marked by a strong assimilation policy at the hands of nation states, theSami are bringing back to the public dimension activities and practices which had long been relegated to the private sphere and,consequently, almost disappeared. Language has emerged as oneof the most important features in Sami cultural revitalization processes. This paper aims at examining the linguistic landscapeof Márkomeannu and the importance of the toponym Gállogieddiin the light of the region’s historical context. It will also explorethe concept that characterized the 2018 edition of Márkomeannu.The home page of the festival reads: “It’s 2118 and the World isabout to collapse”. According to this narrative, Gállogieddi was presented as the last safe place for the Sami people. This conceptconstituted the festival’s theme and was introduced to the publicthrough the display of art, the use of language and the physicalconstruction of a stage merged with the festival location. Bysetting Márkomeannu in a dystopian future, the organizersemployed a wide range of concepts and approaches, spanning fromthe promotion of ecological awareness to ethno-political claims inthe form of decolonisation. Based on the data collected during myfieldwork, my analysis addresses the display of material and non-material Sami cultural heritage. The analysis of Márkomeannu2018 narratives provides a unique insight into contemporary Samiethno-political activism and into the means employed to developand convey a shared Sami identity. Such an analysis provides adiscussion of the interplay between cultural belonging, language proficiency, the symbolic value of cultural practices and ethno- political aspirations in a North Sami context.